1993
DOI: 10.1002/neu.480241102
|View full text |Cite
|
Sign up to set email alerts
|

Developmental analysis reveals labial and subradular ganglia and the primary framework of the nervous system in nudibranch gastropods

Abstract: Previous ultrastructural observations on late stage larvae of dorid nudibranchs (Gastropoda, Opisthobranchia) revealed two pairs of ganglia within the base of the foot that do not have obvious counterparts in existing descriptions of other gastropod larvae [Chia and Koss (1989). Cell Tiss. Res. 256:17-26.] One of these ganglionic pairs has been implicated in the initiation of settlement preceding metamorphosis [Arkett et al. (1989). Biol. Bull. 176:155-160.] By examining neurogenesis in sequential larval stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Sections through progressively older larval stages (compare Figs 9, 10 with Figs 14-16) show this to be incorrect. These observations underscore the fact that the proximal portion of what is called the foot rudiment in young nudibranch larvae is actually presumptive ventral lip tissue (also see Page 1993).…”
Section: Larval Retractor Muscle (Lrm)mentioning
confidence: 72%
“…Sections through progressively older larval stages (compare Figs 9, 10 with Figs 14-16) show this to be incorrect. These observations underscore the fact that the proximal portion of what is called the foot rudiment in young nudibranch larvae is actually presumptive ventral lip tissue (also see Page 1993).…”
Section: Larval Retractor Muscle (Lrm)mentioning
confidence: 72%
“…In Ilyanassa (Lin and Leise, 1994;Leise, 1996) and in the sea hare Aplysia californica (Marois et al, 1993), a distinct apical ganglion has been identified that lies above the dorsal cerebral commissure. This apical ganglion is most likely a developmental outgrowth of the trochophore apical plate (Raven, 1966) and an evolutionary enlargement of an apical or cephalic sensory organ like the ones described in other gastropods (Conklin, 1897;Fretter and Graham, 1962;D'Asaro, 1969;Bonar, 1978a,b;Morse et al, 1980;Bickell and Kempf, 1983;Chia and Koss, 1984;Marois and Carew, 1990;Kempf et al, 1991;Page, 1992aPage, , 1993Page, , 1994. Both Aplysia and Ilyanassa have relatively long-lived planktotrophic veligers that are large at metamorphic competence in comparison to the non-feeding larvae of many of their opisthobranch relatives.…”
Section: Discussionmentioning
confidence: 95%
“…An apical organ has been reported in some of the Gastropoda (Bonar 1977(Bonar , 1978Chia and Koss 1984;Kempf et al 1991Kempf et al , 1997Lin and Leise 1996a, b;Marois and Carew 1997c;Moor 1983;Page 1993;Raineri 1995;Raineri and Ospovat 1994) and the Bivalvia (Raineri 1995;Raineri and Ospovat 1994) as well as many other swimming invertebrate larvae (see for example, Hay- Schmidt 1990a-c, 1995Lacalli 1981Lacalli , 1994. In many molluscs (Bonar 1978;Chia and Koss 1984;Kempf et al 1997;Leise 1996;Marois and Carew 1997a, b) and other invertebrates (see Lacalli 1994), the apical organ possesses flask-or vase-shaped cells with protruding cilia at the epithelial surface.…”
Section: Apical Organmentioning
confidence: 95%